Advanced Nanopharmaceutical Intervention for the Reduction of Inflammatory Responses and the Enhancement of Behavioral Outcomes in APP/PS1 Transgenic Mouse Models - Jun Li; Dongqing Huang; Wanchen Liao; Yulin Wang; Yibiao Liu; Ping Luan (Pharmaceutics)
Background: The excessive accumulation of Aβ plays a critical role in the development of Alzheimer’s disease. However, the therapeutic potential of drugs like curcumin is often limited by low biocompatibility and BBB permeability. In this study, we developed a nanomaterial, BP-PEG-Tar@Cur, which was designed to enhance the biocompatibility of (curcumin) Cur, target Aβ, and augment BBB permeability through near-infrared (NIR) photothermal effects. Methods: Soluble Aβ, ThT fluorescence, and Aβ depolymerization fluorescence experiments were conducted to evaluate the ability of BP-PEG-Tar@Cur to inhibit Aβ aggregation and dissociate Aβ fibrils. Cell uptake assays were performed to confirm the targeting ability of BP-PEG-Tar@Cur towards Aβ. In vitro mitochondrial ROS clearance and in vivo detection of inflammatory factors were used to assess the anti-inflammatory and antioxidant properties of the nanodrug. Water maze behavioral experiments were conducted to evaluate the effect of BP-PEG-Tar@Cur on spatial memory, learning ability, and behavioral disorders in AD mice. Results: The nanodrug effectively inhibited Aβ aggregation and dissociated Aβ fibrils in vitro. BP-PEG-Tar@Cur demonstrated efficiency in curbing ROS overproduction in mitochondria and dampening the activation of microglia and astrocytes triggered by Aβ aggregation. Water maze behavioral experiments revealed that BP-PEG-Tar@Cur enhanced spatial memory, learning ability, and alleviated behavioral disorders in AD mice. Conclusions: Collectively, these findings demonstrate that BP-PEG-Tar@Cur has the potential to be an effective targeted drug for inhibiting Aβ aggregation and improving cognitive impairment in AD mice.